A New Segment of the Trochlear Nerve: Cadaveric Study with Application to Skull Base Surgery - Tubbs, R. Shane; Veith, Philip; Griessenauer, Christoph J.; Loukas, Marios; Cohen-Gadol, Aaron A. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objectives The trochlear nerve is important to preserve during approaches to the skull base. Traditionally, this nerve has been divided into cisternal, cavernous, and orbital segments. However, the authors anecdotally observed an additional segment during routine cadaveric dissections. Therefore, they performed this study to better elucidate this anatomy.Design Twenty latex-injected cadaveric sides (10 adult cadavers) were dissected with the aid of an operating microscope. Standard microdissection techniques were used to examine the course of the distal cisternal and precavernous segments of the trochlear nerve.Setting Cadaver laboratory.Main Outcome Measures Measurements were made using a microcaliper. Digital images were made of the dissections.Results The authors identified a previously undescribed segment of the trochlear nerve in all specimens. This part of the nerve coursed between the entrance of the trochlear nerve into the posterior corner of the oculomotor trigone to the posterior wall of the cavernous sinus. This segment of trochlear nerve was, on average, 4 mm in length.Conclusions The authors have identified a new segment of the trochlear nerve not previously described. They propose that this be referred to as the trigonal segment. Knowledge of the microanatomy of the trochlear nerve is useful to skull base surgeons.
Keywords: microanatomy; cranial nerves; trochlear nerve; neurosurgery